Nepal’s 2072 Federal Constitution: What are the implications for governance of the agricultural sector? - Kyle, Jordan; Resnick, Danielle (International Food Policy Research Institute, 2018)
In September 2015, Nepal’s Constituent Assembly passed a new constitution aimed at transforming Nepal from a unitary country into a federal republic with three levels of government: the federation, the province, and the local level. This institutional shift will have wide-ranging social, political, and economic implications for the country. However, this brief focuses specifically on the implications of these federal reforms for the agricultural sector and the Ministry of Agriculture (MoAD). Agriculture is the backbone of the Nepali economy, providing a livelihood for approximately two-thirds of the population, contributing one-third of the country’s GDP, and constituting over half of its exports. With greater authority and autonomy granted to more subnational units of government, ensuring that the agricul-tural sector is guided by coordinated planning, retains sufficient human capacity, and receives adequate fiscal resources will be of para-mount importance during the transition to a federal republic. Consequently, this brief addresses how the sector can be restructured to meet the constitutional provisions while simultaneously ensuring that MoAD delivers on its agricultural objectives, especially those out-lined in its Agricultural Development Strategy (ADS).